Assessment of farmers’ willingness to pay for bundled climate insurance solutions in Sri Lanka - Aheeyar, Mohamed M. M.; Amarasinghe, Upali A.; Amarnath, Giriraj; Alahacoon, Niranga; Prasad, S.; Dissanayake, A. (International Water Management Institute, 2023)
With the increasing frequency and intensity of climate-related disasters, several social protection and livelihood resilience tools have been tested to reduce agricultural risks. The findings of this study are based on the initial bundled climate insurance solutions pilot conducted in five districts in Sri Lanka (Anuradhapura, Vavuniya, Monaragala, Kurunegala and Ampara) in 2021 with the support of Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). The project intervention was designed to reduce production risks and enhance agricultural resilience through the roll-out of an index insurance product bundled with hybrid seeds and mobile-based weather and agronomic advisories. The research assessed farmers' willingness to pay (WTP) for weather index insurance (WII) solutions with bundled choices as a risk transfer tool with due consideration to the diversity and heterogeneity of the farming population. The report informs the scaling opportunities of bundled climate insurance choices, including product design and implementation among smallholder farmers and reduction of production risks in designing and implementing WII products. The study findings confirm the majority of farmers' perceptions of high climate risk, but the degree of risk is variable between areas and different segments of people. Farmers’ age, gender, farming experience, levels of education, land size operated, and household income form the major factors characterizing the diversity and risk exposures. Attention to gender and social equity issues is important in the design and delivery of insurance products so that the benefits of the interventions reach most of the farming population; this can ensure achievement of the larger development objectives of equity and fairness to disadvantaged people including women. Farmers are experiencing high or very high levels of variability in crop yield, input prices and output prices. However, the differences in willingness to experiment with innovations to minimize the risks and adopt risk-taking approaches to minimize production risks and strengthen livelihood resilience indicate the requirement for carefully designed insurance products. Awareness creation is a prerequisite for this intervention to be a sustainable one. About 80% of farmers are willing to enroll in crop insurance programs, but a major inhibiting factor is the lack of trust in insurers. The amount that farmers are willing to pay as an insurance premium is in the range of 1-2% of the sum insured for the majority of farmers. Bundling insurance with farm support services could be the primary strategy for transitioning insurance programs to be a financially viable and sustainable adaptation strategy, and for upscaling these programs.